Graphene Oxide for Adsorptive Ultrafiltration Membranes (Journal of Applied Membrane Science & Technology, 2023)
Adsorptive ultrafiltration membrane is an emerging field that holds great promise for achieving high efficiency removal of various pollutants such as metal ions and organic pollutants. As a result, significant research efforts have been directed towards the utilization of GO due to its unique properties including good hydrophilicity, large surface area, excellent chemical and mechanical stability which can impart better membrane properties and performance. Recent advances in this field revealed that the utilization of graphene oxide (GO) is highly beneficial in improving key membrane properties including surface charge, hydrophilicity, water permeability as well as the adsorption performance. Therefore, this short review provides valuable insight into the performance of GO/GO modified-based membranes, GO/polymeric-based membrane and GO-modified/polymeric-based membrane for various pollutants. The application of GO in ultrafiltration (UF) membranes is anticipated to provide an attractive and viable route towards achieving high performance adsorptive UF membranes for water and wastewater treatment.
Keywords: Graphene oxide, adsorptive membrane, ultrafiltration, ions; heavy metals